Zanele Muholi - Muholi, Zanele 1972-; Allen, Sarah; Nakamori, Yasufumi (Tate Publishing, 2020)
Glossary -- The queer spectacular : Zanele Muholi and visual redress / Candice Jansen -- Only half the picture -- Community and collectivity -- Uphathe umphako -- ukhumbul' ekhaya / Pamella Dlungwana -- Being -- Letter III : the archive other/wise / Renee Mussai -- Faces and phases -- Thinking activism : Zanele Muholi and queer photography histories / Sarah Allen -- Brave beauties -- Queering space through photography : Zanele Muholi's colour portraits / Yasufumi Nakamori -- Queering public space -- See anew : religion, marriage and funerals / Sindiwe Magona -- The skin they live in / Elvira Dyangani Ose -- Somnyama Ngonyama -- Another approach is possible / Sarah Allen -- Zanele Muholi and Katarina Pierre : a conversation -- Chronology / Sarah Allen and Bongani Matabane
Published on the occasion of the exhibition Zanele Muholi at Tate Modern, London 5 November 2020 - 7 March 2021 ; Maison Européenne de la Photographie, Paris, 17 March - 6 June 2021 ; Martin Gropius Bau, Berlin, 16 July - 31 October, 2021; Bildmuseet, Umeå, 26 November 2021 - 17 April 2022
Keywords: Muholi, Zanele -- 1972-; Person of Color -- Motiv; Homosexualität -- Motiv; Porträtfotografie; Transsexualität -- Motiv; Muholi, Zanele / Exhibitions; Photography / Exhibitions; Sexual minorities; Ausstellungskatalog -- Tate Modern -- 05.11.2020-07.03.2021 -- London; Ausstellungskatalog -- Maison Européenne de la Photographie -- 17.03.2021-06.06.2021 -- Paris; Ausstellungskatalog -- Martin Gropius Bau -- 16.07.2021-31.10.2021 -- Berlin; Ausstellungskatalog -- Bildmuseet -- 26.11.2021-17.04.2022 -- Umeå; Bildband